PENERAPAN ART THERAPY MEMBATIK COLET SEBAGAI UPAYA MEMELIHARA FUNGSI KOGNITIF LANSIA DI POSYANDU BAROKAH, KELURAHAN KLAMPIS NGASEM, KECAMATAN SUKOLILO, KOTA SURABAYA, PROVINSI JAWA TIMUR: The Application of Art Therapy Batik Colet as An Effort to Maintain Elderly Cognitive Functions in Posyandu Barokah, Kelurahan Klampis Ngasem, Kecamatan Sukolilo, Kota Surabaya, Provinsi Jawa Timur - Makhfudli; Kusnul Chotimah; Zenitha Rani; Elida Ulfiana (Jurnal Pengabdian Masyarakat Kesehatan, 2020)
Klampis Ngasem is one of the areas in East Surabaya, precisely in Sukolilo sub-district, Surabaya. The target group in the community partnership program (PKM) is the Elderly Posyandu "Barokah" in RW 3. Problems that occur in the Elderly Barokah Posyandu are less varied activities and innovation so that some elderly are less interested and bored to follow routinely as indicated by the presence of the elderly < 75%, the absence of efforts to prevent dementia that is carried out regularly and continue for the elderly, lack of elderly knowledge about changes in cognitive function and efforts to maintain cognitive function so as to prevent dementia, and the availability of leisure time for the elderly in addition to routine posyandu activities and those that have not been utilized to be useful and productive. The solution to overcome these problems is through the application of Art Therapy to make colet batik. The purpose of this community service is to help express themselves, maintain the cognitive function of the elderly and provide new skills in making batik as an activity in the Posyandu Elder Barokah Klampis Ngasem Village. The activities carried out are screening to see the cognitive function of the elderly using Mini mental state examination (MMSE) and clock drawing test (CDT), counseling about prevention of dementia which includes knowing dementia, prevention of dementia, and art therapy, batik colet training with demonstration methods, and simulation. The results of batik colet will be processed again with the help of cadres or the elderly who have sewing skills to be used as sofa pillowcases. From this process, a work or product will be produced from the batik colet method.